Consumption of Less Than 10% of Total Energy From Added Sugars is Associated With Increasing HDL in Females During Adolescence: A Longitudinal Analysis. Issue 1 (26th February 2014) - Lee, Alexandra K.; Binongo, José Nilo G.; Chowdhury, Ritam; Stein, Aryeh D.; Gazmararian, Julie A.; Vos, Miriam B.; Welsh, Jean A.
Abstract : Background: Atherosclerotic changes associated with dyslipidemia and increased cardiovascular disease risk are believed to begin in childhood. While previous studies have linked added sugars consumption to low high‐density lipoprotein (HDL), little is known about the long‐term impact of this consumption. This study aims to assess the association between added sugars intake and HDL cholesterol levels during adolescence, and whether this association is modified by obesity. Methods and Results: We used data from the National Heart Lung and Blood Institute's Growth and Health Study, a 10‐year cohort study of non‐Hispanic Caucasian and African‐American girls (N=2379) aged 9 and 10 years at baseline recruited from 3 sites in 1987‐1988 with biennial plasma lipid measurement and annual assessment of diet using a 3‐day food record. Added sugars consumption was dichotomized into low (0% to <10% of total energy) and high (≥10% of total energy). In a mixed model controlling for obesity, race, physical activity, smoking, maturation stage, age, and nutritional factors, low compared with high added sugar consumption was associated with a 0.26 mg/dL greater annual increase in HDL levels (95% CI 0.48 to 0.04; P =0.02). Over the 10‐year study period, the model predicted a mean increase of 2.2 mg/dL (95% CI 0.09 to 4.32; P =0.04) among low consumers, and a 0.4 mg/dL decrease (95% CI −1.32 to 0.52; P =0.4) among high consumers. Weight category did not modify this association ( P =0.45). Conclusion: Low added sugars consumption is associated with increasing HDL cholesterol levels throughout adolescence.